2020
DOI: 10.1021/acsami.0c13576
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of Inverted Perovskite Solar Cells with a Modified PEDOT:PSS Hole Transport Layer

Abstract: Organic–inorganic hybrid perovskite solar cells (PSCs) has achieved the power conversion efficiency (PCE) of 25.2% in the last 10 years, and the PCE of inverted PSCs has reached >22%. The rapid enhancement has partly benefited from the employment of suitable hole transport layers. Especially, poly­(3,4-ethenedioxythiophene):poly­(styrenesulfonate) (PEDOT:PSS) is one of the most widely used polymer hole transport materials in inverted PSCs, because of its high optical transparency in the visible region and low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(76 citation statements)
references
References 140 publications
0
74
0
Order By: Relevance
“…The other fitting peaks at 164.2 eV and 165.3 eV corresponded to the signal of S2p 3/2 and S2p 1/2 in PEDOT. 40 After methanol treatment, the peak intensity of 164.2 eV and 165.3 eV increased significantly, and that of 168.1 eV and 169.3 eV remained constant without changing. The relative ratio of PEDOT and PSS were obtained by calculating the peak intensity and peak area of the fitting peaks.…”
Section: Resultsmentioning
confidence: 89%
“…The other fitting peaks at 164.2 eV and 165.3 eV corresponded to the signal of S2p 3/2 and S2p 1/2 in PEDOT. 40 After methanol treatment, the peak intensity of 164.2 eV and 165.3 eV increased significantly, and that of 168.1 eV and 169.3 eV remained constant without changing. The relative ratio of PEDOT and PSS were obtained by calculating the peak intensity and peak area of the fitting peaks.…”
Section: Resultsmentioning
confidence: 89%
“…Indium doped Tin Oxide -ITO), it is easily processable from aqueous solution by spin coating deposition techniques, and allows for achieving record efficiencies in LEDs [6] and optoelectronic devices in general. [12] However, the hygroscopic and acidic (pH~1.5) nature of PEDOT:PSS [13] leads to a rapid degradation of the device anode. [14] In particular, its acidity and the absorption of water molecules promote the etching of the indium from the ITO/PEDOT:PSS interface, then causing the indium diffusion and ultimately leading to fast deterioration of the device.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(3,4‐ethylenedioxythiophene):poly(styrenesulfonate) or PEDOT:PSS, is one of the most commonly used HTLs in perovskite solar cells because of its high optical transparency in the visible region, low processing temperature, surface wettability, mechanical flexibility, and ability to yield high performance devices. [ 4 ] In this study, we examined the effect of PEDOT:PSS on the structural stability of methylammonium lead iodide (CH 3 NH 3 PbI 3 ) films towards humidity exposure. After just 1 day of humidity exposure, X‐ray diffraction (XRD) analysis revealed that the CH 3 NH 3 PbI 3 active layer in contact with PEDOT:PSS began to transition from its tetragonal structure to a cubic structure.…”
Section: Introductionmentioning
confidence: 99%